(untitled) (Annals of Medical Research, 2021)
Aim: This study was conducted to determine the factors affecting clinical education of nursing students and to evaluate their learning processes from their own perspectives. Materials and Methods: This study, in which the phenomenology pattern based on the qualitative design was used, was carried out with fourth-year nursing students studying at a university in eastern Turkey. In the study, sample selection was not made the number of participants was determined according to the data saturation. The data were collected from a total of 30 nursing students who agreed to participate in the study. The thematic analysis method was used to evaluate qualitative data. NVIVO 10 program was used for the transcription and thematic analysis of the interviews held in the virtual classroom environment. Results: The sample of the study was composed of 15 female and 15 male students aged between 21 and 25 years. As a result of thematic analysis, 5 main interrelated themes emerged: (1) Effective and reassuring communication; (2) Adaptation to real working environment; (3) Nurses with high self-confidence; (4) transition to professionalism, and (5) recognizing competencies, strengths, and limitations. Conclusion: The results showed that clinical experiences increased the communication skills of the students, helped them to adapt to the real work environment, gave them self-confidence and practicality, and enable them to gain different experiences. Students’ statements pointed out that clinical practice improves the students in many aspects and is a holistic process.